Tools and techniques for improving the assessment of exposure to food chemicals - Lambe, Joyce (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2000)
Exposure assessments are an integral part of risk assessment and are essential for protecting consumer health and factilitating international trade. The aim of this thesis was to explore the potential usefulness of a number of tools and techniques for improving exposure assessments and their interpretation. A food ingredient database was designed using a relational database management system. Ingredient listings for over 4000 brand foods were obtained and entered in the database in addition to information on permitted conditions of use of additives. A number of tasks were selected to demonstrate the usefulness of the database. The tasks included screening, refining exposure assessments and describing patterns of qualitative additive usage.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin